Supersaturated “water-in-salt” hybrid electrolyte towards building high voltage Na-ion capacitors with wide temperatures operation - Sennu, Palanichamy (2022)
Aqueous asymmetric supercapacitors (ASC) is considered to fulfill the safety and high energy-power requirements simultaneously towards building next-generation storage devices. One of the most attractive electrolytes is multiple ion-based water-in-salt (WIS) solutions, which are steadily conquering the field of rechargeable batteries/capacitors. Stabilizing the pH value is one of the efficient ways to improve the energy density of the charge storage system by widening the operating potential. In this line, we report that acetate ions could help to neutralize the pH of sodium(I)bis(fluorosulfonyl)imide-based WIS electrolyte by diluting the free water molecules without any precipitation or recrystallization, and allow to widen the operating potential window from ~2.7 to 3.1 V. The Physico-chemical properties of mixed anions-based electrolytes are explored from confocal-Raman and Nuclear magnetic resonance studies. In addition, we performed ab-initio density functional theory calculations to study the co-ordination environment. Apparently, the acetate (OAcˉ) ions show a stronger interaction with Na+ ion compared to weakly coordinating imide (FSIˉ) analogues. The Na0.44MnO2 and prosopis juliflora derived activated carbon (PJAC) based ASC, and PJAC based symmetric supercapacitor (SSC) using mixed WIS electrolyte is cycled up to 5000 times. Further, the influence of environmental conditions (60 and −20 °C) is also studied in detail for the WIS based electrolyte for both ASC and SSC.